Ita'leem : evaluation on usability and emotions - Machfud, Fitria Maulida (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2015)
The study of usability and emotion evaluation has been around and received significant attention in the past decade, and so thus the study of e-learning usability evaluation. Many studies also relate the users' psychology factors such as motivation to the usability evaluation. However, limited attention had been given to the studies that relate emotions with e-learning usability evaluation. By adapting some variables from Rogers' innovation- decision process model, Zaharias' usability evaluation model, and Sandanayake and Madurapperuma's conceptual model for e-learning, this study attempts to unfold and understand the relationship between e-learning usability attributes and Kansei emotions. The main goal is to investigate how iTa'leem usability attributes affect its user's emotions, and what type of emotions that have emerged after using iTa'leem. This study also determine the relationship between the users' (in this case students) prior conditions, personal characteristics, and communication channels and the evaluation of iTa'leem usability attributes, as well as between e-learning usability attributes and Kansei negative and positive emotions. This study conducted using a survey method by using paper-based and online questionnaires. International Islamic University Malaysia e-learning system namely iTa'leem was selected in the study to be evaluated and to investigate its effect on students' emotions. Three groups of independent variables namely prior conditions, personal characteristics, and communication channels were statistically investigated to see the relation with the usability attributes evaluation. Five web usability attributes -navigation, learnability, accessibility, consistency, and visual design- and seven instructional design variables –interactivity, content and resources, multimedia usage, learning strategies design, feedback, instructional assessment, and learner guidance and support- were examined. Kansei emotions, which comprise to negative and positive emotions, were also examined. This study found that there is no significant correlation between variables in the communication channels with iTa'leem usability evaluation. Much of the rationale was deemed to be caused by the respondents' familiarity with the functions of iTa'leem and also by homogeneous data of the respondents. This study also found that web usability variables were significantly correlated and had negative relation with confused, rigid, depressed, complicated, and boring, while instructional design variables were significantly correlated and showed negative relation only with boring. Nevertheless, web usability variables and all of the instructional design variables were positively and significantly correlated with all the positive emotions. These were assumed to be caused by the respondents' positive perception on iTa'leem usability attributes.